Islamister i åpnere landskap: Hvilken rolle i det nye Midtøsten? - Utvik, Bjørn Olav (Politik, 2012)
The political successes of Islamists following the Arab uprisings of 2011 makes understanding Islamism more important than ever. ey have long been central to oppositional politics in the Arab world. Now they may well become a dominant factor in the emerging new regimes. A necessary starting point is to recognise that the Islamists played a pivotal role in the Arab spring from the start. Furthermore, to grasp the possible ways in which the Islamists may in uence developments to come, research must turn away from essentialising their Islamic ideology and discover the contradictory impulses driving these complex and dynamic social movements.